2019
DOI: 10.1037/pas0000707
|View full text |Cite
|
Sign up to set email alerts
|

Self-ratings of face recognition ability are influenced by gender but not prosopagnosia severity.

Abstract: The University of Gloucestershire accepts no liability for any infringement of intellectual property rights in any material deposited but will remove such material from public view pending investigation in the event of an allegation of any such infringement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 42 publications
1
9
0
Order By: Relevance
“…However, it is important to note that our sample would have excluded anyone who reported having prosopagnosia, which may appear co-morbidly at rates greater than expected by chance. In addition, it is possible that individuals with DTD generally have some issues with face processing that are simply not captured by the task we employed 41 , or this is indicative of a bias in evaluating one's own abilities 42 . The Cambridge Face Memory task employed in the present study utilizes static face stimuli, with peripheral information (e.g., hair, ears) removed.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is important to note that our sample would have excluded anyone who reported having prosopagnosia, which may appear co-morbidly at rates greater than expected by chance. In addition, it is possible that individuals with DTD generally have some issues with face processing that are simply not captured by the task we employed 41 , or this is indicative of a bias in evaluating one's own abilities 42 . The Cambridge Face Memory task employed in the present study utilizes static face stimuli, with peripheral information (e.g., hair, ears) removed.…”
Section: Discussionmentioning
confidence: 99%
“…Famous faces: The famous faces test has previously been used in our published work (e.g. [12,[55][56][57]). Participants were presented with 60 famous faces suitable for the UK population, one at a time, on a computer screen.…”
Section: Methodsmentioning
confidence: 99%
“…A wide variety of techniques have been used to assess these individuals (for a recent review, see [7]), with a minority of authors relying on self-reported anecdotal evidence alone (e.g., [8]). While respectable associations have more recently been reported between multi-item subjective ratings of face recognition ability and objective measures (e.g., [9]), it is nevertheless clear that some “typical” performers erroneously under-rate their face recognition ability and self-refer for DP assessment [10,11]. Most authors therefore agree that self-rating or anecdotal evidence of DP should always be supplemented by objective measures of face recognition performance [4,12], although the proportion of confirmed diagnoses versus false alarms has not yet been examined in a large group of individuals.…”
Section: Introductionmentioning
confidence: 99%